Family business debates : multidimensional perspectives across countries, continents and geo-political frontiers - Montiel Mendez, Oscar Javier; Tomaselli, Salvatore; Soto Maciel, Argentina (Emerald Publishing Limited, 2022)
The family business arena is dynamic. Family business owners, managers, and practitioners need to be aware of changing management approaches, processes, and strategies to allow them to respond to global competition in an increasingly chaotic world - as emphasised by the COVID-19 pandemic - whilst maintaining their businesses unique character, culture, and attributes. Family Business Debates provides a novel, ground-breaking approach to diverse and contemporary topics in current business management research, focusing on family enterprises to study both the positive and negative aspects of such commercial structures. Each chapter explores specific themes as they relate to family businesses and the authors developing a comprehensive and far-reaching perspective of family businesses from experts around the world, showcasing highly controversial topics in today's global debate within family business and management. Offering unrivalled coverage of contemporary aspects of family business, Family Business Debates offers a unique focus on theory and applied research in family firms, particularly considering and reviewing the impact of research on policy and practice globally. It aims to communicate the latest family business research and knowledge worldwide for the benefit of scholars and family business practitioners.